Dietary supplementation with 2-hydroxy-4-methyl(thio) butanoic acid and DL-methionine improves productive performance, egg quality and redox status of commercial laying ducks - Yanan Zhang; Zhiwei Zhuang; Tahir Mahmood; Yves Mercier; Yongyan Jin; Xuebing Huang; Kaichao Li; Shuang Wang; Weiguang Xia; Shenglin Wang; Miao Yu; Wei Chen; et al. (Animal Nutrition, 2023)
This experiment aimed to study the effects of supplemental methionine sources, 2-hydroxy-4 methyl(thio) butanoic acid (HMTBa) and DL-Methionine (DL-Met), on productive performance, egg quality, and redox status of laying ducks. A total of 792 healthy 25-wk-old Longyan laying ducks with similar body weights were randomly allotted to 11 treatment groups. Each treatment group had 6 replicates of 12 ducks. The trial lasted for 16 wk. Ducks were fed a basal deficient diet (Met: 0.24%; Met + Cys: 0.51%) or supplemented with DL-Met or HMTBa at 0.05%, 0.12%, 0.19%, 0.26%, and 0.33% of diet, respectively. Compared with the basal diet, supplementation with either DL-Met or HMTBa increased the average egg weight, egg mass, and decreased feed to egg ratio during the whole trial period (P < 0.05). Albumen weight and its ratio to total egg weight were increased, but yolk and shell ratio, albumen height, Haugh unit and shell breaking strength were decreased (P < 0.05). Dietary DL-Met or HMTBa supplementation increased taurine, methionine, leucine, tryptophan and arginine content, and decreased serine and lysine content in plasma (P < 0.05). The redox status of laying ducks was improved by enhancing the glutathione peroxidase and catalase activities, glutathione content and its ratio relative to glutathione (oxidized) content and decreasing malondialdehyde content and increasing mRNA expression of superoxide dismutase-1, glutathione peroxidase-1, hemeoxygenase-1 and nuclear factor-like 2 in liver and ileum with the supplementation of DL-Met or HMTBa (P < 0.05). Liver health status measured by average area proportion lipid droplet was improved with supplementation of DL-Met or HMTBa (P < 0.05). Villus height and villus height to crypt depth ratio in the ileum and the ileal gene expression of tight junction protein and occludin were increased with DL-Met or HMTBa supplementation (P < 0.05). Taken together, these results suggested that the efficacy of dietary supplementation of HMTBa was similar to DL-Met, and it ranged from 98% to 100% for productive performance and egg albumen ratio in laying ducks (25 to 41 wk).